Multimodal Cyberbullying in TikTok Comments: A Descriptive Qualitative Analysis - Sari, Angel Aulia; Alya, Hikmah; Sihotang, Rica Octaviani; Rafi'a, Uswatun; Putri, Dian Marisha (Journal of English Language and Education, 2025)
Cyberbullying in social media has become an increasingly visible issue, particularly on platforms where communication relies on rapid, multimodal expression. However, existing studies tend to focus mainly on verbal hostility, leaving limited attention to how meaning is constructed through the combination of text, emojis, and images. This study aims to describe how these semiotic resources collectively convey bullying intent in TikTok comment sections. Using a qualitative descriptive approach, the data were analyzed through multimodal meaning interpretation and categorized according to types of online aggression. The findings show that sarcasm, mockery, and ridicule were often expressed not through words alone but strengthened through patterned emoji use, exaggerated punctuation, and visual layering. The study concludes that multimodal symbols play a significant role in shaping online bullying practices and should be considered in digital literacy and prevention strategies.